2018
DOI: 10.1097/ogx.0000000000000546
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Fresh Versus Frozen Embryos in Ovulatory Women

Abstract: (Abstracted from N Engl J Med 2018;378:126–136) A previous randomized controlled trial involving women with polycystic ovary syndrome (PCOS) compared fresh-embryo transfer with elective freezing of all embryos followed by frozen-embryo transfer. The data showed that frozen-embryo transfer had a higher live-birth rate in these women compared with fresh-embryo transfer. Whether frozen-embryo transfer also increases live-birth rates among ovulatory women with infertility without PCOS is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…The primary endpoint for this analysis was non-inferiority of LBR when comparing euploid vs mosaic embryos. Assuming a LBR of 45% for uniformly euploid embryos vs 42.5% for moderate or low degree mosaics 16 , assuming a 1:1 sampling ratio for the two groups, and a planning non-inferiority margin of 7.5% 17,18 , we calculated that 421 embryos per group would guarantee a power of at least 90% for a significance level fixed at 5%. This sample size was also >90% powered to claim non-inferiority in the miscarriage rate between control and test group with a margin of 2%, assuming a 10% rate for uniformly euploid embryos and 15% for moderate/low mosaics.…”
Section: Resultsmentioning
confidence: 99%
“…The primary endpoint for this analysis was non-inferiority of LBR when comparing euploid vs mosaic embryos. Assuming a LBR of 45% for uniformly euploid embryos vs 42.5% for moderate or low degree mosaics 16 , assuming a 1:1 sampling ratio for the two groups, and a planning non-inferiority margin of 7.5% 17,18 , we calculated that 421 embryos per group would guarantee a power of at least 90% for a significance level fixed at 5%. This sample size was also >90% powered to claim non-inferiority in the miscarriage rate between control and test group with a margin of 2%, assuming a 10% rate for uniformly euploid embryos and 15% for moderate/low mosaics.…”
Section: Resultsmentioning
confidence: 99%
“…Frozen embryo was conducted when fresh embryo transfer was unsuccessful. A study of 2157 women in a multicenter randomized trial demonstrated that the risk of moderate or severe ovarian hyperstimulation syndrome was lower among patients who underwent the FET in comparison with fresh embryo transfer 18 . Evidences suggested that embryos were frozen in a fresh IVF cycle, then were thawed and transferred into uterus in the proper condition might improve the pregnancy rates 19‐21 .…”
Section: Discussionmentioning
confidence: 99%
“…A study of 2157 women in a multicenter randomized trial demonstrated that the risk of moderate or severe ovarian hyperstimulation syndrome was lower among patients who underwent the FET in comparison with fresh embryo transfer. 18 Evidences suggested that embryos were frozen in a fresh IVF cycle, then were thawed and transferred into uterus in the proper condition might improve the pregnancy rates. [19][20][21] Furthermore, the occurrence of pregnancies after FET can lead to fewer complications such as lower rates of antepartum hemorrhage, and better neonatal outcomes including higher birth weight and lower risk of perinatal death.…”
Section: Multivariable Logistic Analysis Of Livebirth Ratesmentioning
confidence: 99%
“…Remaining embryos are in most cases cryopreserved and available for future embryo transfers [5]. Use of frozen and thawed embryo transfers (FET) was previously considered to lead to fewer successful pregnancies as compared to fresh embryo transfer, but technical advances such as innovative freezing techniques, vitrification [8,9] and visual embryo selection of embryos or blastocysts have improved the success rate of FET to a level on par with that of fresh embryo transfers [10,11]. In women with the polycystic ovary syndrome (PCOS), the success rate after FET is substantially higher than that after fresh embryo transfers [12].…”
Section: In Vitro Fertilization (Ivf)mentioning
confidence: 99%